Assessment of Concentration of Airborne Heavy Metals in the Workplace and of Operational Efficiency of a Scrap Iron and Steel Smelter - Owoade, Oyediran Kayode (2015)
Energy and material audit, measurement of concentration of suspended particulate matter (SPM) and elemental analysis of the SPM were carried out in a scrap iron and steel smelter in Lagos, Nigeria. This was with the view to assessing the operational efficiency and the occupational exposure of workers in various production processes of the industry to toxic heavy metals.